Factors Affecting for Competitive Advantage of Handicraft Business in Luang Prabang City - THYSAVANG, Bounthan; HOONGSENGPHA, Soudthida; SENGCHAN, Souksamone (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This research is to study the level of ability to create a competitive advantage and the relationship of the factors affecting the competitive advantage of handicraft businesses in Luang Prabang city; using five indicators of entrepreneur capacity theory, these include: proactiveness, Autonomy, risk-taking, innovation, and competitive aggressiveness. Then, using marketing mixed theory (4Ps) including product, price, place, and promotion to analyze the relationship and the factors affecting the competitive advantage of handicraft business in Luang Prabang city. The sample for this research was the entrepreneurs of 84 handicraft shops in Luang Prabang. Five level of Likert Scale of questionnaire was applied to collect data, there is a reliability level of 0.829 (82.9%) and Using SPSS statistical software for data analyzed the frequency, percent, mean, standard Deviation, Pearson Correlation Coefficient and, Multiple Regression Analysis. The result of the research found that: the capacity of the entrepreneur to competitive advantage of handicraft business part appears at a higher level, while the capacity of the competitive advantage of handicraft business indicator shows at the highest level, especially differentiation, cost strategy, and quick response respectively; the ability factors of entrepreneurs that have a linear relationship, the same effect, and result in the creation of a competitive advantage for handicraft businesses in Luang Prabang city include two factors: risk-taking and Proactiveness, while the marketing mixed factor has a linear relationship and has the same result. There is only one factor as the product that affect to create the capacity of competitive advantage for handicraft businesses in Luang Prabang city.